Canadians' perspectives on how much space nature needs - Pamela A. Wright; Farhad Moghimehfar; Alison Woodley (Canadian Science Publishing, 2019)
Determining how much to set aside in a system of protected areas has been widely discussed. In the past, targets that have been set internationally and domestically are best described as politically driven. In recent years, there has been a call to shift towards evidence-based targets for conservation. One element that has been largely missing from this dialogue is public perception of how much to protect. We conducted an online, regionally balanced survey of just over 2000 Canadians to ask about their values for protected areas, including how much they thought was currently and should be protected. Overall, Canadians overwhelmingly agree that protected areas are necessary and think that approximately 50% of land and sea should be protected in Canada and globally. Nation-wide support for a significant increase in the amount of land/sea protected is a new finding in Canada, although consistent with applications of the same survey in other countries. As the timeline for achieving the current 2020 protected area targets approaches, countries are beginning to discuss what targets to set for the next decade. Our findings demonstrate strong public support for significantly scaling up Canada's conservation targets, consistent with ecological evidence.